Coadministration of seasonal influenza and COVID-19 vaccines: A systematic review of clinical studies. Issue 6 (30th November 2022) - Janssen, Cécile; Mosnier, Anne; Gavazzi, Gaëtan; Combadière, Behazine; Crépey, Pascal; Gaillat, Jacques; Launay, Odile; Botelho-Nevers, Elisabeth
ABSTRACT: The lifting of non-pharmaceutical measures preventing transmission of SARS-CoV-2 (and other viruses, including influenza viruses) raises concerns about healthcare resources and fears of an increased number of cases of influenza and COVID-19. For the 2021-2022 influenza season, the WHO and >20 European countries promoted coadministration of influenza and COVID-19 vaccines. Recently, the French Health Authority recommended coupling the COVID-19 vaccination with the 2022-2023 influenza vaccination campaign for healthcare professionals and people at risk of severe COVID-19. The present systematic review examines published data on the safety, immunogenicity, efficacy/effectiveness, and acceptability/acceptance of coadministration of influenza and COVID-19 vaccines. No safety concerns or immune interferences were found whatever the vaccines or the age of vaccinated subjects (65- or 65+). No efficacy/effectiveness data were available. The results should reassure vaccinees and vaccinators in case of coadministration and increase vaccine coverage. Healthcare systems promoting coupled campaigns must provide the necessary means for successful coadministration. Plain Language Summary: The lifting of non-pharmaceutical measures recommended to prevent transmission of SARS-CoV-2 (and other viruses, including influenza viruses) raises concerns about healthcare resources, already under pressure. It also raises fears of an increase in the number of cases of influenza or COVID-19 infection during the winter season. For the 2021–2022 influenza season, the World Health Organization and several European countries promoted concomitant administration in distinct anatomic sites (i.e., coadministration) of influenza and COVID-19 vaccines to avoid additional stress on healthcare systems. In May 2022, the French Health Authority recommended coupling the COVID-19 vaccination with the 2022–2023 influenza vaccination campaign (i.e., starting COVID-19 vaccination at the date of influenza vaccination) for healthcare professionals and people at risk of severe COVID-19, in case of epidemic wave. Coadministration of influenza and COVID-19 vaccines is one of the factors of success for a coupled campaign. The present systematic review examines all published data (articles or reports, clinical trials, or surveys) on the safety, immunogenicity, efficacy/effectiveness, and acceptability/acceptance of coadministration of influenza and COVID-19 vaccines. The PRISMA method was used to collect information. No safety concerns or immune interferences were found whatever the vaccines or the age of vaccinated subjects (65- or 65+). No efficacy/effectiveness data were available. Acceptability and acceptance were good but could be improved. By reassuring vaccinees and vaccinators, these results are expected to favor coadministration and ultimately increase vaccine coverage, thus offering better protection. Healthcare systems promoting coupled campaigns with coadministration must provide the necessary means for their successful implementation.